1991
DOI: 10.1210/endo-129-2-1104
|View full text |Cite
|
Sign up to set email alerts
|

C-Type Natriuretic Peptide (Cnp) in Rats and Humans

Abstract: We have established a specific radioimmunoassay (RIA) for C-type natriuretic peptide (CNP), the third member of the natriuretic peptide family, and have elucidated its tissue distribution and molecular form. In rats, high concentrations of CNP-like immunoreactivity (-LI) were detected in the anterior lobe (19.8 +/- 8.6 pmol/g) and neurointermediate lobe (4.64 +/- 0.74 pmol/g) of the pituitary gland. CNP-LI was present throughout the brain with its high concentrations in the hypothalamus and cerebellum. Small a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
117
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 280 publications
(122 citation statements)
references
References 16 publications
4
117
0
1
Order By: Relevance
“…As for the subtype of the biologically active receptors, the ANP-A receptor is predominantly expressed in PC12 cells, bovine EC, and LLC-PK, cells, whereas the ANP-B receptor is predominant in rat aortic SMC and human mesangial cells. Since CNP is distributed mainly in the brain, 9 the significance of the abundant expression of the ANP-B receptor in mesangial cells and aortic SMC remains to be resolved. However, we have reported that CNP exists in peripheral organs, such as in pituitary, kidney, and colon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As for the subtype of the biologically active receptors, the ANP-A receptor is predominantly expressed in PC12 cells, bovine EC, and LLC-PK, cells, whereas the ANP-B receptor is predominant in rat aortic SMC and human mesangial cells. Since CNP is distributed mainly in the brain, 9 the significance of the abundant expression of the ANP-B receptor in mesangial cells and aortic SMC remains to be resolved. However, we have reported that CNP exists in peripheral organs, such as in pituitary, kidney, and colon.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have reported that CNP exists in peripheral organs, such as in pituitary, kidney, and colon. 9 Therefore, CNP may act as a local regulator through interaction with the ANP-B receptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ANPB receptors have been detected in brain microvessel endothelial cells, but not in aortic endothelial cells, which express ANPA receptors (Vigne & Frelin, 1992). The possible role of CNP (apparently a brain-restricted peptide, Kojima et al, 1990;Komatsu et al, 1991) in the cerebellum and whether CNP interacts with the cerebral microvasculature require further investigation. Although there is evidence for ANP and/or the C-receptor coupling to phosphoinositide turnover in other systems (see Introduction), we were unable to observe an increase in…”
Section: Effects Of Natriuretic Peptides On Cyclic Amp Generationmentioning
confidence: 96%
“…CNP, the third member of natriuretic peptide family, was first purified from porcine brain [18]. While CNP is the primary natriuretic peptide in the human brain [19], it is also produced by vascular endothelial cells [20][21][22] and macrophages [23], and is thought to act as an autocrine/paracrine regulator and as a neuropeptide [19]. Furthermore, analysis of genetically engineered mice of the CNP/GC-B system revealed that CNP and GC-B play a pivotal role in the regulation of endochondral bone growth.…”
Section: Abstract: C-type Natriuretic Peptide (Cnp) Guanylyl Cyclasmentioning
confidence: 99%